Parents’ and teachers’ perception about the impact of school nurse role in Saudi Arabia - Bajamal, Eman; AlShami, Zainab; Aljahdali, Ebtisam; Alotaibi, Maha; Alharthi, Hanan; Alotaibi, Razan (Frontiers in Public Health, 2025)
PurposeTo assess the parent’s and teacher’s perception of the school nurse role in Saudi Arabia.MethodsA cross-sectional study of 305 participants of parents and teachers in Saudi Arabia. Data was collected using a previously tested and validated questionnaire to measure the parents and teacher perception about the role of school nurse.ResultsApproximately 305 participants completed the online questionnaire. The total perception scores ranged from 0.00 to 34.00, with a mean of (M = 27.52, SD = 5.96). The scale demonstrated excellent internal consistency (Cronbach’s α = 0.902; McDonald’s ω = 0.896). Exploratory factor analysis supported a four-factor structure, explaining 58.6% of the total variance. The results revealed that the divorced participants had significantly lower perception of the school nurse’s role than married and widowed participants. Similarly, participants with lower family income demonstrated lower perceptions of the school nurse role than higher family income participants. Additionally, uneducated participants had significantly lower perceptions of the school nurse’s role in providing first aid and emergency care compared with high school education/undergraduate/graduate degree participants.ConclusionThe findings highlight that most participants perceived the school nurse as playing a vital role in delivering comprehensive health services within the school setting. This underscores the significance of strengthening school nursing services to support student well-being and health promotion.